The importance of material properties, nutrient load and shear stress on biofilm formation - Joana Moreira (2015)
Inorganic and biological fouling reduce the performance of heat exchangers leading to frequent process interruptions for equipment cleaning. In order to identify the key parameters affecting bacterial adhesion and biofilm formation, different surfaces and different nutrient loads were tested under static and dynamic conditions. Copper, stainless steel and glass surfaces were assayed under high or low nutrient loads in static conditions or under agitation (shear stress of 0.27 Pa) using Escherichia coli as a model organism. Results show that nutrient load had a higher effect on biofilm maturation than on cell adhesion. It was also found that shear stress is particularly important when copper surfaces are used. For this surface, higher biofilm amounts were obtained in static conditions especially under high nutrient load (4-fold increase when compared to dynamic conditions). This trend was observed since the initial adhesion step. Collectively, results show that for all the tested conditions, surface properties have the most significant effect on cell adhesion and biofilm formation. This effect is more pronounced under low nutrient load and, in most cases, a correlation with surface hydrophobicity was found.